Hubungan antara Neutrofil Limfosit dengan Lama Rawatan dan Angka Kematian Pasien COVID-19 di RSUD Meuraxa Banda Aceh - Evi Maryani; Nur Fitriani; Andri Andri (MEDIA KESEHATAN MASYARAKAT INDONESIA, 2023)
Pendahuluan: Corona virus disease (COVID-19) adalah penyakit yang menyerang sistem pernapasan disebabkan oleh virus SARS CoV-2. Pasien yang terinfeksi COVID-19 mengalami penurunan sistem imun akibat peningkatan rasio neutrofil disertai penurunan limfosit. Hal tersebut dapat mempengaruhi lama rawatan dan kematian pasien. Tujuan pada penelitian ini untuk mengetahui peningkatan dan penurunan rasio neutrofil limfosit (RNL) disertai hubungan terhadap lama rawatan dan kematian pasien COVID-19.Metode: Jenis penelitian deskriptif analitik pendekatan cross sectional pengambilan data dengan purposive sampling pada bulan Januari-Oktober 2021 berjumlah 200 sampel. Data diambil dari catatan rekam medik pasien sesuai kriteria inklusi. Data dalam penelitian ini dilakukan analisis univariat, bivariat, dan multivariat.Hasil: Hasil analisis univariat menunjukkan jumlah pasien dengan RNL >3,13 lebih banyak dibandingkan dengan ≤3,13. Pasien COVID-19 dengan lama rawatan <14 hari lebih banyak dibandingkan ≥14 hari. Pasien yang dirawat dengan status sembuh lebih banyak dibandingan meninggal. Analisis bivariat mendapatkan hasil tidak terdapat hubungan antara RNL dengan lama rawatan dengan nilai p sebesar 0,908 (Lebih dari α 0,05). Akan tetapi, terdapat hubungan antara peningkatan RNL dengan kematian pasien (nilai p = 0,001). Analisis multivariat regresi logistik multinomial pada RNL dan lama rawatan berpengaruh terhadap kematian pasien COVID-19.Kesimpulan: Kesimpulan terdapat hubungan antara peningkatan RNL dengan kematian, tetapi tidak terdapat hubungan antara RNL dengan lama rawatan.Kata kunci: COVID-19, Rasio Neutrofil Limfosit (RNL), lama rawatan, kematian pasien Title: Relationship Between Neutrophil Lymphocytes and Length of Care and Death Rate of Covid-19 Patients in Meuraxa Hospital Banda AcehBackground: Corona virus disease (COVID-19) is a disease that affects the respiratory system caused by the SARS CoV-2 virus. Patients infected with COVID-19 experience a decrease in the immune system due to an increase in the ratio of neutrophils accompanied by a decrease in lymphocytes. This can affect the length of treatment and death of the patient.  to determine the increase and decrease in the ratio of neutrophil lymphocytes (RNL) along with the relationship to the length of treatment and death of COVID-19 patients.Method: This type of descriptive analytical research with a cross-sectional approach, data were collected by purposive sampling in January-October 2021, totaling 200 samples. Data were taken from patient medical records according to the inclusion criteria. The data in this study were analyzed using univariate, bivariate, and multivariate.Result: The results of the univariate analysis showed that the number of patients with RNL >3.13 was higher than that of those with ≤3.13. More COVID-19 patients with a length of stay <14 days than ≥14 days. More patients who were treated with recovery status than died. Bivariate analysis showed that there was no relationship between RNL and length of stay, with a p value of 0.908 (more than α 0.05). However, there is a relationship between increased RNL and patient death (p value = 0.001). Multivariate analysis of multinomial logistic regression on RNL and length of stay has an effect on the death of COVID-19 patients. Discussion: There is a correlation between increased RNL and mortality, but there is no correlation between RNL and duration of stay.Keywords: COVID-19, Neutrophil Lymphocyte Ratio (RNL), length of stay, patient death